2016
DOI: 10.1212/nxi.0000000000000202
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profiles show heterogeneity of interferon-β response in multiple sclerosis patients

Abstract: Objective:To evaluate serum cytokine profiles for their utility to determine the heterogeneous responses to interferon (IFN)–β treatment in patients with multiple sclerosis (MS).Methods:Patients with relapsing-remitting MS (RRMS) or clinically isolated syndrome receiving de novo IFN-β treatment were included in this prospective, observational study. Number of relapses and changes in disability were assessed 2 years prior to and 2 years after initiation of treatment. Sera were collected at baseline and after 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 37 publications
1
31
0
2
Order By: Relevance
“…Additionally, since treatments affect many of these markers (40), it will be critical to have a baseline reading for each patient, and then a longitudinal assessment following treatment, looking at the profile for both relapsing and remitting conditions to determine which markers have the greatest prognostic value for a particular patient. Furthermore, the concentration of some inflammation-related serum biomarkers varies in a circadian manner, thus taking into account the time of day that samples are collected is vital to make meaningful comparisons (41).…”
Section: Biomarkers For Ms Relapsementioning
confidence: 99%
“…Additionally, since treatments affect many of these markers (40), it will be critical to have a baseline reading for each patient, and then a longitudinal assessment following treatment, looking at the profile for both relapsing and remitting conditions to determine which markers have the greatest prognostic value for a particular patient. Furthermore, the concentration of some inflammation-related serum biomarkers varies in a circadian manner, thus taking into account the time of day that samples are collected is vital to make meaningful comparisons (41).…”
Section: Biomarkers For Ms Relapsementioning
confidence: 99%
“…For other MS disease-modifying therapies (DMTs), variable treatment responses have been linked to differences in pre-treatment immune abnormalities. For example, heterogeneity in baseline type I interferon (IFN) and Th17 activity may explain variability in IFN-β responsiveness 10,11 .…”
mentioning
confidence: 99%
“…Investigations over the past 7 years, led by Robert Axtell (a postdoctoral fellow in my lab and then a faculty member at Oklahoma Medical Research Foundation), have stratified the different clinical types of the disease we lump together as relapsing-remitting MS. Axtell and colleagues use a combination of cytokine and chemokine profiles on serum and then advanced bioinformatics. We demonstrated that there is heterogeneity in the levels of a battery of cytokines and chemokines in individuals with relapsing-remitting MS, and the levels provide a signature that correlates with the therapeutic response to IFN-β (109).…”
Section: Discussionmentioning
confidence: 93%
“…So I recommend keeping spirits high with humor. One of my colleagues who employed perhaps the most charming, intelligent and insightful use of humor has been Robert Axtell (109).…”
Section: Discussionmentioning
confidence: 99%